Fluctuations in Plasma Levels of Thrombomodulin in Patients with DIC - Amano, Kagehiro; Tateyama, Masaki; Inaba, Hiroshi; Fukutake, Katsuyuki; Fujimaki, Michio (Thrombosis and Haemostasis, 1992)
Plasma thrombomodulin (TM) has attracted considerable attention as a marker of endothelial cell membrane injury. We examined fluctuations in plasma TM levels in patients receiving therapy for the disseminated intravascular coagulation syndrome (DIC) using an enzyme immunoassay. Sixty healthy controls and 18 patients with DIC were studied.The mean ± SD of the TM values initially measured immediately after the onset of DIC was 42.00 ± 20.85 ng/ml, which was markedly increased as compared with the control value of 15.36 ±4.85 ng/ml (p <0.001).Fluctuations in the TM levels over time were studied after dividing the patients according to the presence or absence of improvement in the underlying disease and improvement or lack thereof in the coagulation findings. Group I showed improvement in both categories, Group II showed improvement only in the latter, and Group III showed no improvement in either category.In Group I, the mean ± SD of initial measured TM levels was 37.02 ±10.12 ng/ml and the mean of final values decreased to 58.9% of the initial value. This decrease was significant by paired Student’s t-test (p <0.01). The initial value in Group II was 45.86 ± 18.86 ng/ml and the final values increased to 117.0% of the initial values, this difference was not significant. The initial value in Group III was 44.48 ±21.53 ng/ml and the final values increased to 143.4% of the former. This increase was significant by paired Student’s t-test (p <0.05). The difference in % fluctuations between Group I and Group III was significant by Wilcoxon’s test (p <0.01).These results suggest that the measurement of plasma TM can be useful in the management of DIC.